Clinical, functional and aberrometric parallels in the treatment of the neovascular form of age-related macular degeneration - M. M. Magomedova; A.-H. D. Aliyev; S. I. Zakieva; Z. N. Maksudova; M. T. Mikailova (Российский офтальмологический журнал, 2024)
Purpose: to analyze clinico-functional and aberrometric parameters of patients with the neovascular form of age–related macular degeneration (nAMD) treated by the anti-VEGF drug brolucizumab. Material and methods. The study involved 59 patients (59 eyes) aged 55 to 75 years, divided into two groups depending on the type of treatment. Group 1 consisted of 25 patients (25 eyes) who had previously received no anti-VEGF therapy and Group 2 had  34 patients (34 eyes) with an active nAMD form, who had previously been given anti-angiogenic therapy with aflibercept. All patients averagely received 5.48±1.5 brolucizumab injections in the “treat and extend” mode: 3 loading injections with monthly checkups followed by elongated intervals reaching 8 weeks. The treatment effectiveness was estimated by the change in maximum corrected visual acuity (MCVA) as measured by precision visometry, the aberrations parameters of the optical system of the eye, and the thickness of the central retinal zone (CRZ). In addition, the height of retinal pigment epithelium (RPE) detachment, the presence of intraretinal fluid (IRF), subretinal fluid (SRF), and fluid under RPE. Results. In group 1, BCVA whose initial value was 0.37 ± 0.16 reached 0.78 ± 0.25 (p = 0.02) by the end of treatment, while in group 2, the value rose from 0.35 ± 0.18 to 0.62 ± 0.22 (p = 0.02). After the 5th injection, Group 1 showed a statistically significant decrease in TCZV (ave. by 270.17 ± 92.37 μm, p=0.05), while Group 2 showed a less pronounced morphological result (a decrease from 480.54 ± 174.22 to 320.32 ± 109.53, p < 0.05). Both groups also showed, after the 5th injection, a decrease in the cumulative frequency of occurrence of various types of fluid (p < 0.02). A decrease in all components of higher order aberrations was also noted after the first 3 injections; this result remained stable until the end of the observation period (p = 0.04). Conclusion. In Group 1 patients, we succeeded in achieving high morphological and functional results and maintaining them at a stable level until the end of the observation period. Group 2, patients with an active nAMD, previously treated with other anti-VEGF preparations, showed a less pronounced, though stable improvement in morphofunctional parameters.